EFFECT OF BACTERIA-PLANT INTERACTIONS AND MINERAL NITROGEN ON PRODUCTIVITY OF THE MIXED SOWINGS IN THE GREY FOREST (SYLVOGENIC) SOILS - O. N. Shkotova (Зерновое хозяйство России, 2018)
One of the reasons of instability of high yields of agricultural crops in the Nechernozem zone of Russia is low soil fertility. In the last years the problem is of great importance because of a sharp decline of mineral fertilizers used by the farms of the country. So, the modern science pays more attention to the study of biologization of agriculture that allows creating highly productive and ecologically sustained agro systems, and using biocoenotic potential of agro coenosis and natural resources of the region more completely and efficiently. The article shows the ways of increase of grain productivity in the mixed sowings of soybean and lupine-barley on 19.2-21.3% and the amount of protein on 30.3-37.9% due to the use of the mixture of symbiotic and associative rhizobacteria and mineral nitrogen (in the dose of N60). It has been determined that in the lupine-barley, soybean-barley and pea-barley sowings the mixtures of the bio medicines and the types (ammonia and nitrate) of mineral nitrogen (in the dose of N60) had a great effect on grain productivity. According to the study we developed and gave agronomically and economically substantiated recommendations on the cultivation of such mixed sowings in the grey forest (sylvogenic) soils as lupine-cereal, pea-cereal and soybean-cereal, which can give high and sustained yields.